Bioeconomy in Textile Industry: Industrial Residues Valorization Toward Textile Functionalization - Ana M. Fernandes; Ana Isabel Pinheiro; Catarina Rodrigues; Carla J. Silva (Recycling)
Industrial residues are sources of functional biopolymers with interesting properties for textile applications. This study aims to evaluate the impact of enzymatic pre-treatment on oil yield and phenolic compounds’ content in an aqueous extraction process, as well as the functional properties incorporated into textiles. This research investigated the influence of residue granulometry, biomass percentage, and the application of enzymatic pre-treatment with different enzymes (cellulase, pectinase, xylanase) individually or in combination. Chestnut hedgehog (CH), tobacco plant stems (TPSs), vine shoot trimmings (VSTs), and beer spent grain (BSG) were explored. For textile functionalization, the extracted oils were incorporated into a bio-based formulation and applied on cotton fabric through pad-dry-cure. For CH, the pre-treatment with cellulase and xylanase achieved an oil yield of 149 and 148 mg oil/mL extract, respectively. With the combination of both enzymes, the richest oil in phenolic compounds was extracted: 1967.73 ± 16.86 mg GAE/g biomass. CH and TPS oils presented an antioxidant activity above 60%, and the functionalized textiles also showed the highest antioxidant potential and a UPF of 30. The textiles presented water repellence and washing fastness. This study demonstrates a sustainable oil extraction method and its potential application in the development of functional textiles.